2015
DOI: 10.3923/mj.2015.36.42
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of Agro-Industrial Wastes as Substrates for Cellulase Production by Bacillus licheniformis MTCC 429

Abstract: The aim of the present investigation was to exploit the cheap agro-waste, sugarcane bagasse as a substrate for cellulase enzyme production using Bacillus licheniformis MTCC 429. The cellulase producing ability of B. licheniformis MTCC 429 was assessed using CMC agar plates. The factors affecting cellulase production were optimized by varying the parameters of incubation period, temperature and pH. The maximum cellulase enzyme production was achieved when the production medium pH was maintained at pH 7.0, tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
(20 reference statements)
0
2
0
2
Order By: Relevance
“…Las celulasas producidas en ambos medios de cultivo presentaron mayores AE cuando la reacción se realizó a pH 7,0 (Figuras 1 y 2), evidenciándose que presentan una mejor actividad que a pH 5,0. Estos resultados coinciden con los publicados para las celulasas producidas por B. licheniformis MTCC429, a partir de residuos agroindustriales (Bala Kumaran et al 2015), por las obtenidas por Pseudomonas sp. y Serratia sp., aisladas de residuos de salvado de trigo (Prabesh et al 2016) y para la producida a partir de Acinetobacter junii GAC 16.2 (Banerjee et al 2020).…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…Las celulasas producidas en ambos medios de cultivo presentaron mayores AE cuando la reacción se realizó a pH 7,0 (Figuras 1 y 2), evidenciándose que presentan una mejor actividad que a pH 5,0. Estos resultados coinciden con los publicados para las celulasas producidas por B. licheniformis MTCC429, a partir de residuos agroindustriales (Bala Kumaran et al 2015), por las obtenidas por Pseudomonas sp. y Serratia sp., aisladas de residuos de salvado de trigo (Prabesh et al 2016) y para la producida a partir de Acinetobacter junii GAC 16.2 (Banerjee et al 2020).…”
Section: Resultados Y Discusiónunclassified
“…Los medios A1 y A2 permiten la producción de celulasas a partir de la cepa C6M2 obteniendo actividades de 30,19 ± 0,61 U/mL y 30,74 ± 0,95 U/mL, que son superiores a las producidas en otros sustratos formulados con residuos agroindustriales. Es así, como las celulasas producidas por B. licheniformis 2D55, en un medio preparado con cáscaras de arroz y bagazo de caña, obtuvieron una actividad CMCasa 0,38 U/mL (Kazeem et al 2017) y otro estudio reportó 0,50 U/mL, para celulasas obtenidas en un caldo CMC con un hidrolizado de bagazo de caña al 5 %, a partir de B. licheniformis MTCC 429 (Bala Kumaran et al 2015).…”
Section: Resultados Y Discusiónunclassified
“…Ibrahim et al [52] in their study found a nearly similar optimum temperature of 37°C for maximum cellulase activity but the incubation time (24 h) for the same was less than the present finding for the bacterium P. aeruginosa . In the study of Kumaran et al [53], optimum pH of 7.0, the temperature of 35°C and an incubation time of 48 h were determined at which the bacterium Bacillus licheniformis MTCC 429 achieve both the maximum cellulase production and activity. The optimum values of pH, temperature, and incubation time for maximum cellulase yield obtained from Kumaran et al [53] found to be more closely to the optimum values found for those same process parameters (pH 6.75, temperatures: 37.5°C and incubation time: 42 h) in the current investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial cellulases have gained more attention than their fungal counterparts for several reasons. Bacterial cellulases are preferred due to their lower production costs compared to fungal cellulases [ 4 , 5 ]. Moreover, bacteria have faster growth rates than fungi, enabling them to reach high cell densities more quickly.…”
Section: Introductionmentioning
confidence: 99%